Use of alternative methods as an inducer of forced molting in laying quail - Oliveira, Ana Beatriz Fonseca de (2023)
The objective was to evaluate alternative methods of qualitative and quantitative feed restriction compared to the conventional technique of forced moulting in Japanese quails for the second production cycle. The forced moulting period lasted 10 days and two 21-day post-molt periods. 72 female Japanese quails were used, at the end of production at 72 weeks of age. The birds were distributed in a completely randomized design with three treatments and four replications each, with six quails per replicate. The experimental treatments were: T1 – birds submitted to three days of fasting with subsequent provision of laying feed ad libitum for seven days; T2 – birds that received controlled feeding (10 g/bird/day) for 10 days; T3 – birds that received rice bran ad libitum for 10 days. Throughout the experiment, all birds were submitted to natural lighting with an average of 12 hours of daily light and water ad libitum and after 10 days of molting, laying feed was provided ad libitum. The use of T2 (10 g/bird/day of laying ration) and rice bran as an alternative food in the forced molt program was feasible. Even the weight loss being below the recommended, the birds that received 10 g of poultry feed/day and rice bran ad libitum showed similar post-moult performance and egg quality results to birds that were fasted, in addition to enabling better conditions. of animal welfare